2016
DOI: 10.1002/andp.201600201
|View full text |Cite
|
Sign up to set email alerts
|

Pump spectral linewidth influence on stimulated Brillouin scattering (SBS) and stimulated Raman scattering (SRS) and self‐termination behavior of SRS in liquids

Abstract: The threshold, temporal behavior, and conversion efficiency of stimulated Brillouin scattering (SBS) and stimulated Raman scattering (SBS) in three liquids (benzene, hexane, and dimethyl sulfoxide) and two crystals (calcite and barium nitrate) have been investigated under three largely different spectral linewidth conditions. Pumped with 532‐nm and nanosecond duration laser pulses of ≤ 0.01 cm−1 linewidth, only SBS can be generated in all tested liquids with a high nonlinear reflectivity. However when the pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition, to examine the temporal behavior of SRS in chlorobenzene, the simultaneous temporal waveforms of the pump laser pulse, transmitted pump pulse, and the forward SRS pulse were measured (Figure S3). The result indicated that the self-terminating behavior of SRS was generated in liquids …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to examine the temporal behavior of SRS in chlorobenzene, the simultaneous temporal waveforms of the pump laser pulse, transmitted pump pulse, and the forward SRS pulse were measured (Figure S3). The result indicated that the self-terminating behavior of SRS was generated in liquids …”
mentioning
confidence: 99%
“…The result indicated that the self-terminating behavior of SRS was generated in liquids. 26 Kerr self-focusing effect is always taking place together with the SRS process. Kerr self-focusing is of major importance for the onset of SRS.…”
mentioning
confidence: 99%